Empat Aspek Dukungan Keluarga Mampu Meningkatkan Motivasi Pengobatan Pasien Kanker Dalam Menjalani Kemoterapi Dan Radiasi Selama Pandemi Covid 19 - Werdani, Yesiana Dwi Wahyu; Prasetiani, Abigael Grace (Universitas Tribhuwana Tunggadewi, 2023)
The COVID-19 pandemic has caused chronic diseases patient such as cancer survivors vulnerable to death, on the other hand, cancer treatment programs must continue to prevent cell metastasis. The study aimed to prove the effect of four aspects of family support on increasing the motivation for completing chemotherapy and radiation therapy during the COVID-19 pandemic. This is a correlation study with a cross-sectional approach. Samples were cancer patients living at the Indonesian Cancer Foundation, East Java Surabaya Branch who met the inclusion criteria set, which amounted to 50 people. The instruments used are the Family Support Scale (FSS) and the Treatment Motivation Questionnaire (TMQ) which have been tested for validity and reliability. The linear regression test found that all aspects of family support had a significant effect on treatment motivation. Informational support (r = 0.387, p = 0.005), emotional support (r = 0.386, p = 0.006), instrumental support (r = 0.372, p = 0.008), appraisal support (r = 0.367, p = 0.009). Four aspects of family support can provide enthusiasm and motivation for patients to continue carrying out cancer treatment in a pandemic situation 19.